2015
DOI: 10.1111/mmi.13153
|View full text |Cite
|
Sign up to set email alerts
|

Cell surface‐associated aggregation‐promoting factor from Lactobacillus gasseriSBT2055 facilitates host colonization and competitive exclusion of Campylobacter jejuni

Abstract: SummaryCampylobacter jejuni, one of the most common causes of gastroenteritis worldwide, is transmitted to humans through poultry. We previously reported that Lactobacillus gasseri SBT2055 (LG2055) reduced C. jejuni infection in human epithelial cells in vitro and inhibited pathogen colonization of chickens in vivo. This suggested that the LG2055 adhesion and/or co-aggregation phenotype mediated by cell-surface aggregation-promoting factors (APFs) may be important for the competitive exclusion of C. jejuni. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 72 publications
(109 reference statements)
1
29
0
Order By: Relevance
“…For another Lactobacillus species, L. gasseri SBT2055, it was suggested that this strain reduces C. jejuni colonization in chickens by competitive exclusion (44,45). In the current study, coadministration of the robust colonizing isolate L. reuteri CSF8 with the E. coli vaccine also improved vaccine efficacy.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…For another Lactobacillus species, L. gasseri SBT2055, it was suggested that this strain reduces C. jejuni colonization in chickens by competitive exclusion (44,45). In the current study, coadministration of the robust colonizing isolate L. reuteri CSF8 with the E. coli vaccine also improved vaccine efficacy.…”
Section: Discussionmentioning
confidence: 52%
“…Previous reports also described an antagonistic relationship between C. jejuni and Lactobacillus species (44,45), including L. reuteri (46). Thus, L. reuteri probiotic strain CSF8 was also selected by using an experimental design validated for comparison of the ecological competitiveness of L. reuteri strains in chickens in vivo (39).…”
Section: Discussionmentioning
confidence: 99%
“…In case of campylobacteriosis, probiotics (in particular lactobacilli) have been shown to co-aggregate with C . jejuni thus reducing the adhesion to and invasion of the intestinal epithelial cell layers and to suppress motility which is essential for pathogenicity 24, 35 . The modes of actions of the corresponding probiotic formulations have been examined for decades.…”
Section: Discussionmentioning
confidence: 99%
“…jeuni it has been conclusively demonstrated that L . gasseri SBT2055 inhibits invasion of epithelial cells by co-aggregation in vitro and counteracts pathogenic colonization in chicken 23, 24 . Furthermore, production of organic acids (mainly lactic acid) by probiotic lactobacilli exerts killing of C .…”
Section: Introductionmentioning
confidence: 99%
“…44 Calabi et al 45 reported Clostridium diffcile adhered to collagen I via its surface layer proteins, and hence collagen I is potential to be a good target for competitive exclusion of pathogens that adhere to ECM and/or submucosa in the GIT. To ensure the results shown by Lehri et al, 43 in vivo experiments should be performed in the future as was reported by Nishiyama et al, 46 in which Lactobacillus gasseri SBT2055 reduced C. jejuni infection in chicken by competitive binding to the host cells and/or co-aggregation with the pathogen in mediation of cell-surface aggregation-promoting factors.…”
mentioning
confidence: 99%